The Asymmetric Effects of Real and Nominal Uncertainty on Inflation and Output Growth: Empirical Evidence from Bangladesh - Shah, Said Zamin; Baharumshah, Ahmad Zubaidi; Habibullah, Muzafar Shah; Hook, Law Siong (International Journal of Economics and Financial Issues, 2017)
This study examines an empirical analysis of the causal links and volatility spillovers between inflation, output growth and their uncertainties in Bangladesh by utilizing the AR(p)-EGARCH model for the period 1993-2014. The study shows that EGARCH version provides the best statistical fit by investigating that volatility is variable and asymmetric than symmetric. The empirical results show an overwhelming support for Friedman-Ball hypothesis that inflationary shocks affect inflation uncertainty positively. Both inflation and output growth generate output uncertainty which is detrimental for real economic activity while nominal uncertainty (real uncertainty) is positively (negatively) affecting output growth. Finally, output uncertainty is reducing inflation uncertainty while there is no effect from the opposite side. Our estimated results suggest that policy makers should adopt dynamic stabilization policies in order to reduce a rise in inflation and to achieve economic stability for stimulating output growth further. Keywords: Inflation, output growth, uncertainties, Bangladesh, AR(p)-EGARCH. JEL Classifications: C32, C51, C52, E10, E30